Tolstoy and the religious culture of his time : a biography of a long conversion, 1845-1887 - Medzhibovskaya, Inessa, 1964- (Lexington Books, 2008)
The first book-length study on the subject in any language, Tolstoy and the Religious Culture of His Time treats Tolstoy's experience as a massive philosophical and religious project rather than a crisis-laden tragedy. Inessa Medzhibovskaya explainsthe evolution of Tolstoy's religious outlook based on his ongoing dialogue with the tradition of conversion in Europe and Russia, as well as on the demands of his own heart, mind, and spirit. The author contextualizes Tolstoy's conversion, comparing hispattern of religious conversion with that of other notable religious converts-Saint Paul, Saint Au.